Investigação dos efeitos da posição de impressão e geometria da matriz no processo de extrusão polimérica com pellets visando a manufatura aditiva - Oliveira, Renan Oscar de (Universidade Federal de São Carlos, 2023)
The trend of additive manufacturing (AM), also known as 3D printing, has been gaining prominence in the industry in recent years, consequently, a growing front of studies has been conducted to ensure quality and productivity. There are several efforts in different directions to expand knowledge, breaking barriers in 3D printing, specifically in Fused Deposition Modeling (FDM), such as the manufacture of parts using directly fused pellets (FPM) and the increase of the dimensional scale of the printed parts, towards the production of large volume parts (LFAM-Large-Format Additive Manufacturing). Exploiting the advantages of 3D printing using polymeric pellet material directly, this study uses ABS (acrylonitrile butadiene styrene) as a raw material and a laboratory single-screw extruder to investigate the effects of flow rate on varying the print position and final geometry of the extruded filament as a function of the dedicated nozzle geometric shape. The patterns were analyzed from a series of 72 extrusion conditions. By collecting and analyzing the operating data, the linear relationship between screw rotation and extruder mass flow rate was confirmed, and it was possible to get the characteristic values of this equipment. The internal pressure in the screw is strongly influenced by the screw rotation speed. A variation of the density of the extruded material was identified at rotations lower than 20 rpm. For rotations equal to or greater than 20 rpm, a stability of the density is noted, confirming the rotation range of 30 - 60 rpm suggested by the manufacturer. From the geometric shape of the extruded filaments, it was evident the influence of the viscoelastic effect of the polymeric material (Barus effect) and proved its normal expansion ratio directly related to the geometric section shape of the nozzle, in agreement with the numerical simulations in previous studies. With the dedicated geometric nozzle shape, it was possible to extrude filaments with final quadratic geometry, which favors in decreasing the void density. The understanding and control of these phenomenons lead to advances and breakthroughs regarding the mastery of direct extrusion processes with polymer pellets in distinct printing positions, final extruded filament geometry, improved planar adhesion between strip and layer faces, and shorter extrusion time in medium and large formate 3D printing.
Investigation of the effects of printing position and die geometry in the polymeric extrusion process with pellets aiming at additive manufacturing
Keywords: Manufatura Aditiva; Extrusão (FDM); Polímeros Pellets (FPM); Posição de Extrusão; Matriz de Extrusão Customizada; Geometria do Filamento; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO